Influence of 2,4,6-trinitrotoluene (TNT) concentration on the degradation of TNT in explosive-contaminated soils by the white rot fungus Phanerochaete chrysosporium. - Spiker, J K (1992)
The ability of Phanerochaete chrysosporium to bioremediate TNT (2,4,6-trinitrotoluene) in a soil containing 12,000 ppm of TNT and the explosives RDX (hexahydro-1,3,5-trinitro-1,3,5- triazine; 3,000 ppm) and HMX (octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine; 300 ppm) was investigated. The fungus did not grow in malt extract broth containing more than 0.02% (wt/vol; 24 ppm of TNT) soil. Pure TNT or explosives extracted from the soil were degraded by P. chrysosporium spore-inoculated cultures at TNT concentrations of up to 20 ppm. Mycelium-inoculated cultures degraded 100 ppm of TNT, but further growth was inhibited above 20 ppm. In malt extract broth, spore-inoculated cultures mineralized 10% of added [14C]TNT (5 ppm) in 27 days at 37 degrees C. No mineralization occurred during [14C]TNT biotransformation by mycelium-inoculated cultures, although the TNT was transformed.